Multiple cerebral hydatidosis - Genolet, Christian; Giménez, Maximiliano; Piatti, Giuliano; Rivamar, Gabriel; Schiro, Marcos; Couto, Juan Pablo (Revista Argentina de Neurocirugía, 2025)
Background: hydatidosis is a zoonosis caused by the parasite Echinococcus granulosus, with a high prevalence in various regions of the world. The main organs affected are the liver and lungs, with cerebral localization being rare, representing only 2% of cases.Objectives: to describe a case of multiple cerebral hydatidosis and analyze the published literature.Case description: we present the case of a 16-year-old male patient from a rural area with headache, hemiparesis, and difficulty walking for 3 months. Imaging studies revealed multiple bilateral cerebral cysts, as well as cardiac, renal, pancreatic, and muscle cysts. The diagnosis of hydatidosis was based on imaging studies, serological tests, and pathological anatomy.Surgery: six cerebral cysts were surgically removed using the Dowling technique. The patient recovered without complications, and albendazole treatment continued postoperatively.Conclusion: multiple cerebral hydatidosis without liver or lung involvement is an extremely rare presentation. Early diagnosis and a multidisciplinary approach, including medical and surgical treatment, are essential for the successful management of this condition.
Keywords: Albendazole; cerebral hydatidosis; Dowling technique; Echinococcus granulosus